PENGARUH HARGA, STRATEGI PROMOSI, ULASAN KONSUMEN DAN KEMUDAHAN APLIKASI TERHADAP KEPUTUSAN PEMBELIAN PADA MARKETPLACE SHOPEE - Veronica, Pingky (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2021)
Ease of internet technology and with the current Pandemic situation, changing purchasing behavior directly into online purchases. Online purchases can be done by utilizing the Shopee Marketplace. Shopee Marketplace is an online application that can be accessed anywhere and anytime. Shopee became the application most downloaded by the global community, as many as 203 million in 2021. The purpose of this study was to determine the effect of prices, promotional strategies, usual conusmen, and ease of application on purchasing decisions in the Shopee marketplace at Alma Ata Yogyakarta University students. Data analysis using multiple linear regression with data processing using the SPSS 25 application, with a total of 100 respondents. Sampling techniques in the study are purposive sampling. By using a Likert measurement scale. This study shows that prices, consumer reviews, ease of applications have a positive and significant effect on online purchasing decisions on the Shopee Marketplace. While the promotion strategy has a positive and insignificant effect on purchasing decisions in the Shopee Marketplace. With the results of research the author suggests to managerial Shopee to increase efforts in building consumer reviews that are more positive and a reflection of the quality of stores and products expected by consumers. And expected to increase promotion in aspects of the availability of vouchers and other promotions with the aim of being able to provide more attraction to consumers